Development of interactive learning media based on Canva and Genially for earth structure material in fifth grade elementary school - Norvenky, Sherina; Carlian, Yayan; Mahmud, Muhammad Rifqi; Pratiwi, Inne Marthyane (International Conference on Elementary Education, 2025)
Limitations in innovative learning media can affect the learning process, resulting in low learning motivation and conceptual understanding. Therefore, this study aims to develop interactive learning media based on Canva and Genially for fifth-grade elementary school students in Natural andSocial Sciences (IPAS), specifically for material on the structure of the earth and atmospheric layers. The focus of this study is to create more interesting and effective learning media as a solution to the lackof interactivity in the learning process. This study uses a research and development (R&D) approach with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation,and Evaluation. Data collection techniques were carried out through interviews, observations, literature reviews, and questionnaires. The initial design of the innovative learning media was based on the Multimedia Learning theory proposed by Richard E. Mayer, using the Canva and Genially applications. The media created was validated by experts, which showed that the validation results were in theacceptable category, with media validity test results of 88%, material validity of 92,5%, learning expert validity of 82,5%. The results of the student response questionnaire on a limited scale were 87,5%, indicating a high level of practicality and interest. This shows that interactive learning media is feasible to use but with some revisions and further large-scale trials.